THE ROLE OF MYCORRIZATION IN THE DEVELOPMENT OF BLASTING DISEASE (Pyricularia oryzae), GROWTH AND PRODUCTION OF SEVERAL VARIETIES OF GOGO RICE: PERAN MIKORIZA TERHADAP PERKEMBANGAN PENYAKIT BLAS (Pyricularia oryzae), PERTUMBUHAN DAN PRODUKSI BEBERAPA VARIETAS PADI GOGO - Rimbun, Epriani (Agrifarm: Jurnal Ilmu Pertanian, 2024)
ABSTRACT This study aims to evaluate the role of mycorrhiza in the development of blast disease, growth and production of gogo rice. The research was carried out at the Dry Land Experimental Garden and at the Forestry Laboratory, Faculty of Agriculture, Halu Oleo University. The research method used a Split Plot Design (RPT) in the form of a Randomized Block Design (RAK) consisting of two factors. The first factor is the main mycorrhizal plot which consists of two levels, namely M0 and M1. The second factor as a subplot is a variety consisting of four levels, namely V1: Situ Patenggang, V2: Situ Bagendit, V3: Besu and V4: Nggalaru, each treatment was repeated 3 times so that there were 24 treatment units. Each treatment unit consisted of 50 plants per plot. Variables observed included blast disease development, growth, production and percentage of root infection. The results of the research showed that there was an interaction effect of mycorrhizal inoculation and variety on the development of blast disease, growth and production had a very significant effect on plant height. Variety has a very significant effect on disease severity. The highest disease severity was obtained from the Situ Bagendit variety, 97.35%. Mycorrhiza has a positive effect on production. Mycorrhizal infection in the roots of upland rice plants can be seen in the percentage of root infections in gogo rice plants. The average percentage of infection of the Situ Patenggang variety is 0.56% with the highest percentage. The percentage of mycorrhizal infection on the roots of upland rice plants indicates that the mycorrhiza used is compatible with gogo rice plants. Keywords— Mycorrhiza, Pyricularia Oryzae, Gogo Rice